Damage mechanism and electro-elastic stability of LiNbO3 crystals irradiated with 6 MeV Xe23+. Issue 37 (8th June 2020) - Tian, Shiwei; Jiang, Chao; Chen, Feifei; Yu, Fapeng; Li, Yanlu; Cheng, Xiufeng; Wang, Zhengping; Zhao, Xian
Abstract : Bulk LiNbO3 (LN) crystals could maintain their electrical and electro-elastic properties even under hard irradiation. Abstract : The trigonal lithium niobate crystal (LiNbO3, LN) is a multi-functional material that possesses excellent nonlinear optical, pyroelectric and piezoelectric properties. In this work, the irradiation damage mechanism and stability of the electro-elastic properties of LN crystals irradiated with different doses (10 13 –10 16 ions per cm 2 ) of 6 MeV Xe 23+ ions were evaluated for potential piezoelectric applications under irradiation conditions below 650 °C. The vacancy formation energies for Li, O, and Nb atoms are much lower than the irradiation energy of 6 MeV, with the lowest vacancy formation energy being obtained for Li, so that a high concentration of vacancies will be generated in LN upon irradiation. The vacancies narrow the band gap and decrease the electrical resistivity after irradiation. In contrast to the electrical resistivity, the relative dielectric permittivity of the LN crystal was found to increase with increasing irradiation dose, due to the weakened chemical bonds and distorted crystal structure, as confirmed by X-ray photoelectron spectroscopy. Despite the irradiation, the effective piezoelectric coefficients of bulk LN crystal remain nearly unchanged, indicating the favorable properties of LN for use under irradiation conditions at temperatures up to 650 °C.